COLON SPECIFIC DELIVERY OF COMBINATION OF 5-FLUOROURACIL AND CELECOXIB: PREPARATION, CHARACTERIZATION, AND IN VITRO CYTOTOXICITY ASSAY - BANSAL, VIKAS; KAMBOJ, ANJOO; MADAN, JITENDER (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: 5-Fluorouracil (5-FU) and celecoxib (Cel) combination offered additive effect in the treatment of colon cancer. However, physicochemical and biopharmaceutical attributes of both drugs deliver suboptimal concentration at the site of action. The objective of the current study is the development of a microparticulate drug delivery system loaded with a combination of 5-FU and Cel to achieve prolonged drug delivery in colon cancer. Methods: 5-FU and Cel combination were loaded in Eudragit coated chitosan (CH) microspheres (MSs) and characterized. Results: The average particle size of the MSs was in the range of 2.7±0.9μm to 4.8±1.1μm. A substantial drug encapsulation efficiency of 71.30±2.3% as obtained for 5-FU as compared to 35.20±1.9% of Cel in the tailored microparticles. The drug loading capacity of 6.5 mg/10 mg and 2.3 mg/10 mg was obtained for 5-FU and Cel, respectively. By Eudragit S 100 (Ed) coating, significant pH-dependent release profile was achieved, and no drug release was observed in simulated gastric and intestinal fluids. The developed MSs exhibited the release of 92.1±2.9% of 5-FU in 8h whereas 18.9±0.7% Cel was found to be released from the developed MSs. The drug-loaded MSs exhibited appreciable potency against HT-29 cells with an IC50 value of 35.9 μM. Conclusion: The results indicated that these microparticles are a promising vehicle for selectively targeting drugs to the colon in the chemotherapy of colon cancer.